(untitled) (Research, Society and Development, 2020)
This study aims to identify the health profile of participants in groups from the Health Academy in a city in the interior of RS. Data collection was carried out through closed quantitative questionnaires, developed by the author of the article, and the most common possible pathologies among regulars were analyzed, such as; hypertension, low blood pressure, type I and II diabetes, hypoglycemia, osteoporosis, tendonitis, spine problems, cervical and cardiovascular problems. The instrument was applied in groups of the Academia da Saúde Program of the 05 participating ESF, reaching 100% of the groups and approximately 90% of the total users of the same in the city. Based on the results obtained, it can be said that each group has a different profile, this being a precaution to be taken by a future Physical Educator who will join the program or intern, plan the activities that may or may not be carried out depending on the profile of the group to be worked on, preserving the safety of the participants.